EVALUATION OF THE EFFICIENCY OF COMBINATION THERAPY WITH HYALURONATES IN PATIENTS WITH HIP OSTEOARTHROSIS - A G Shusharin; V M Prokhorenko; V V Morozov; A I Shevela (Научно-практическая ревматология)
Objective: to make the results of treatment for coxarthrosis better via prosthetic synovial fluid replacement, by improving drug delivery into the joint cavity. Subjects and methods. The clinical trial enrolled 359 outpatients treated for coxarthrosis. A control group comprised 50 patients receiving the intraarticular combination drug Alflutop under ultrasound (US) guidance. A study group included 309 patients treated using a new three-stage procedure. At stage 1, the patients were given periarticular injections of the current enzyme preparation longidase with a hyaluronidase activity of 3000 IU. At stage 2, postisometric relaxation sessions were performed. At stage 3, after defining the optimal access, synovial fluid prosthetic devices were inserted into the joint cavity under US guidance (a total of 2-3 injections) once weekly. To evaluate the efficiency of the developed treatment option, the authors used a number of standard tests, WOMAC index, Leken's index, integral index of lower limb dysfunction, needs for nonsteroidal anti-inflammatory drugs; total treatment scores given by a physician and a patient; quality of life estimation using the SF-36 questionnaire. Results. The developed treatment option could significantly reduce the clinical and functional WOMAC index and Leken's index, and inadequate joint function in the immediate period and a year after the treatment performed. It also considerably improved quality of life in patients with hip osteoarthrosis, which appeared as a significant increase of its rating according to eight SF-36 scales during more than a year.